2013
DOI: 10.1136/annrheumdis-2013-203803
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoproteins inhibit urate crystal-induced inflammation in mice

Abstract: Objectives To investigate the effects and mechanisms of action of high-density lipoproteins (HDL) in monosodium urate (MSU) crystal-induced inflammation -that is, gouty inflammation, in vivo. Methods Air pouches raised on the backs of mice were injected with MSU crystals or tumour necrosis factor (TNF) in the presence or absence of HDL and/or interleukin (IL)-1 receptor antagonist (IL-1Ra) for 3 h. Leucocyte count and neutrophil percentage in pouch fluids were measured using a haemocytometer and May-Grünwald-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…Whereas further studies are needed to better understand the exact molecular mechanism and integral components of HDL that are required, we have described a new pathway through which HDL could suppress inflammation caused by CC in atherosclerotic plaque. Results from this study may also help to explain the beneficial effects of HDL that have been described in other crystalline diseases, such as gout and silicosis …”
Section: Discussionmentioning
confidence: 62%
“…Whereas further studies are needed to better understand the exact molecular mechanism and integral components of HDL that are required, we have described a new pathway through which HDL could suppress inflammation caused by CC in atherosclerotic plaque. Results from this study may also help to explain the beneficial effects of HDL that have been described in other crystalline diseases, such as gout and silicosis …”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, HDL do not affect the production of the crystal-induced anti-inflammatory factor IL-1Ra. Unlike other lipoproteins, HDL may act not only by adhering to the surface of the crystals, but also through a direct interaction with the inflammatory cells (Scanu et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory cytokine assessment in SF demonstrated that IL-1Ra levels are higher in gouty patients than in osteoarthritis patients (Chen et al, 2011). The injection of MSU crystals into a murine air pouch causes IL-1Ra production after 3 h, although the levels detected are not sufficient to inhibit the inflammatory effect of IL-1β at that same time point (Scanu et al, 2015). In vitro stimulation of monocytes/macrophages by synthetic MSU, CPP and basic calcium phosphate (BCP) crystals induces a rapid increase in pro-inflammatory cytokines such as IL-1β, IL-8 and IL-6, whereas longer periods are required to release high levels of IL-1Ra (a personal observation).…”
Section: Introductionmentioning
confidence: 99%
“…Some CXC chemokines, of which interleukin-8 (CXCL8) is the classic type, attract polymorphonuclear leukocytes to sites of acute inflammation. There are a number of chemokines and their receptors identified to have some roles in acute gouty arthritis, such as CCL2, CCL3, CCL4, CXCL1,CXCL2, CXCL8(IL-8), CXCL10, CXCL16, CCR5, CXCR2, CXCR4, and CXCR6 [54][55][56][57].…”
Section: Mirnas and Chemokinesmentioning
confidence: 99%